Traditions of writing research - Bazerman, Charles (Routledge, 2010)
Traditions of Writing Research €reflects the various styles of work offered at the Writing Research Across Borders conference. This volume, like the conference that it grew out of, will bring new perspectives to the rich dialogue of contemporary research on writing and advance understanding of this complex and important human activity.